The teachings of John Paul II and the paradoxes of the right to life in the International Human Rights discourse - Jorge Nicolás Lafferriere (Chrześcijaństwo-Świat-Polityka)
The right to life has a unique and outstanding importance in the International Human Rights Law. However, at the same time, this right suffers from new threats and contradictions. In this paper, I will address these paradoxes, concerning the moment, in which the legal protection of the human being begins; the tendency to accommodate the beginning of life to biotechnological interests; the manipulation of language, as well as the relativization of the right to life and the pretensions of justifying abortion and euthanasia as a requirement of the right to life. I will offer an assessment of these paradoxes in the light of the Magisterium of John Paul II, and I will end with four signs of hope and commitment at the beginning of the 21st century in relation to the protection of the right to life.